eSport consumption and sponsor brand equity: the mediating role of congruence - Yeayoung Noh; Yoonji Ryu; Kyungyeol Kim (Frontiers in Psychology, 2025)
The present study examines how eSport consumption influences sponsor brand equity through the mediating role of sponsor-eSport congruence. Specifically, the current study investigates the mediating effects of congruence in the relationship between two types of eSport consumption—live attendance and live streaming—and three types of sponsor brand equity: brand loyalty, brand image, and brand awareness. Data were collected from 1,353 Korean eSport fans. The findings reveal that live attendance positively affects brand image but has no significant effect on brand loyalty or brand awareness. Similarly, live streaming enhances brand image but does not influence brand loyalty or brand awareness. Mediation analyses indicate that congruence fully mediates the relationship between live attendance and both brand loyalty and brand awareness, while partially mediating the relationship between live attendance and brand image. Congruence fully mediates the relationship between live streaming and both brand loyalty and brand awareness, while partially mediating the link between live streaming and brand image. These results indicate the critical role of congruence in translating eSport consumption into stronger sponsor brand equity, offering valuable insights for both researchers and practitioners navigating the rapidly growing eSport sponsorship landscape.